Depletion time of antibiotic residues in milk from Manchega dairy ewes - Althaus R.L.; Molina P.; Soutullo H.; Peris C.; Martínez M.; Fernández N. (Production systems and product quality in sheep and goats, 2001)
The use of pharmacological products, which may contaminate milk and affect its quality, is a standard practice to treat various sheep diseases. The aim of the study was to analyse the depletion time of an antibiotic solution injected in ewes to treat mastitis. Twelve Manchega ewes at the end of the lactation period (5th month) were injected with a colistine, spiramycin and dexametasone solution (Mames parenteralÒ). Milk samples from a single daily milking (morning) were collected after 24 hours from the antibiotic treatment and for the following 14 days and analysed by the microbiological methods BRTÒ and DelvotestÒ. Our preliminary results indicated that depletion time of colistine and spiramycin in milk collected from treated ewes, determined by BRTÒ and DelvotestÒ methods, was 10 days, and it depended on the daily milk production of the ewes.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)